1999
DOI: 10.1091/mbc.10.10.3097
|View full text |Cite
|
Sign up to set email alerts
|

Caldesmon Inhibits Nonmuscle Cell Contractility and Interferes with the Formation of Focal Adhesions

Abstract: Caldesmon is known to inhibit the ATPase activity of actomyosin in a Ca(2+)-calmodulin-regulated manner. Although a nonmuscle isoform of caldesmon is widely expressed, its functional role has not yet been elucidated. We studied the effects of nonmuscle caldesmon on cellular contractility, actin cytoskeletal organization, and the formation of focal adhesions in fibroblasts. Transient transfection of nonmuscle caldesmon prevents myosin II-dependent cell contractility and induces a decrease in the number and size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
158
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(178 citation statements)
references
References 94 publications
16
158
3
Order By: Relevance
“…10 The actin cytoskeleton in eukaryotic cells operates as a tension-sensing molecular device and has an important regulatory role on cellular contractility and adhesion-dependent signaling via caldesmon modulation. 40 The contractile functions are carried out by modulating cellular tensional integrity (tensegrity) without disrupting the cel- Pilocytic astrocytoma ϩ lular structural integrity. 41 However, alterations of CALD1 expression and the molecular mechanisms leading to such alterations in the context of neoplastic angiogenesis remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The actin cytoskeleton in eukaryotic cells operates as a tension-sensing molecular device and has an important regulatory role on cellular contractility and adhesion-dependent signaling via caldesmon modulation. 40 The contractile functions are carried out by modulating cellular tensional integrity (tensegrity) without disrupting the cel- Pilocytic astrocytoma ϩ lular structural integrity. 41 However, alterations of CALD1 expression and the molecular mechanisms leading to such alterations in the context of neoplastic angiogenesis remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In non-muscle cells, simulation of CALD1 overexpression by transfection of full-length l-CaD results in the inhibition of cell contractility and interferes with Rho A-mediated formation of stress fibers and focal adhesions. 40 The co-activated caldesmon isoforms induce an overexpression of the protein and could have a synergetic effect on the cellular contractility of the vascular components, enhancing the permeability of microvessels, and consequently facilitate the extravasation and migration of cancer cells. Moreover, both an increase in cellular calcium concentration and caldesmon phosphorylation cause dissociation of caldesmon from actin and results in weakening most of caldesmon's properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, increased expression of caldesmon stabilizes micro®laments (Warren et al, 1995(Warren et al, , 1996, and caldesmon levels are decreased in many transformed cells, as shown in Figure 3, and by others (Button et al, 1995;Novy et al, 1991). More recent studies implicate caldesmon in the regulation of actomyosin contractility and adhesion-dependent signaling in ®broblasts (Helfman et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibiting the Rho pathway and myosin light chain kinase with a variety of small molecules (H-7, ML-7, Y-27632) (Epstein et al, 1999;Rao et al, 2001;Tian et al, 1998) or with bacterial toxins such as C3 (Liu et al, 2005), will uncouple actin from myosin, resulting in relaxation of the cells and disassembly of the actin cytoskeleton. In addition to small molecules and toxins, there are other proteins, such as caldesmon, that uncouple the linkage of actin and myosin II resulting in focal adhesion disassembly and loss of actomyosin contractility (Helfman et al, 1999).…”
Section: Role Of the Trabecular Meshwork Cytoskeleton In Outlfow Facimentioning
confidence: 99%